Necrotic granulomatous pseudotumours in bilateral resurfacing hip arthoplasties: evidence for a type IV immune response. - Pandit, H; Vlychou, M; Whitwell, D; Crook, D; Luqmani, R; Ostlere, S; Murray, D; Athanasou, N (2008)
Clinical, radiological and histological findings were analysed in four patients who developed bilateral pseudotumours following metal-on-metal (MoM) resurfacing arthroplasties of both hips. Using a panel of monoclonal antibodies directed against HLA-DR, macrophages (CD14, CD68), dendritic cells (DC-SIGN, S100, CD11c), B cells (CD20), and T cells (CD3, CD4, CD8), the nature of the heavy inflammatory response seen in these cases was examined. Bilateral masses developed in periprosthetic soft tissues following the second MoM arthroplasty; these were characterised histologically by extensive coagulative necrosis, a heavy macrophage infiltrate and the presence of granulomas containing macrophages and giant cells; there was also a diffuse lymphocyte and variable plasma cell and eosinophil polymorph infiltrate. Immunohistochemistry showed strong expression of HLA-DR, CD14 and CD68 in both granulomatous and necrotic areas; lymphocytes were predominantly CD3+/CD4+ T cells. The clinical, morphological and immunophenotypic features of these necrotic granulomatous pseudotumours, which in all cases develop following a second resurfacing hip arthroplasty, is suggestive of a type IV immune response, possibly to MoM metal alloy components.